PENERAPAN METODE PEMBELAJARAN KOOPERATIF DALAM MENYONGSONG KURIKULUM 2OO4 PADA SISWA KELAS 1 SEMESTER II SMP NEGERI 10 SURAKARTA TAHUN PELAJARAN 2OO4/2005 - Prih Utami, Runtut; Rosyidi, Alvi; Sumanto, Sumanto (BIOEDUKASI, 2006)
AbstractThe aims of this research are to know the ffictiveness of STAD method as one of thecooperative teaching method and compared it with the conventional one. The effectiveness parametersused was the sudent achievement on biology. This research held upon the student of the first grade andof the 2il semester of SMP Negeri 10 Siiakarta in academic yiar of 2004/2005. Clustered randomsampling technique was used upon two classes' i.e the treatment class (using STAD method) andconventional one. Data obtained was then analyzed by t-test.The research concluded that application STAD on facing the curriculum 2004 is a goodteaching method. It raised the student's achievement on biology, statistically showed bJ t o6r"."4) t p6r1= 2.039 > 1.670 with significance of SVo.Key words: Cooperative learning method, Competence based curiculum